Perspectives on colonialism in northwest Greenland - Binachon, Martin, 1998- (2021)
Verkefnið er lokað til 05.05.2031. This thesis questions the structure behind the substantial difficulties the Inughuit, an indigenous people from Avanersuaq (Northwest Greenland), are confronted with. By studying the colonial history of Avanersuaq, it identifies a specific ethnologic discourse which has systematically described the Inughuit as ‘primitive’ Kalaallit (West Greenlanders) since European explorers first encountered the Inughuit. It then assesses how this discourse has justified the gradual exclusion of the Inughuit from policy-making and their assimilation into the West Greenlandic society. This dynamic, initiated by the establishment of a Trading Station in Avanersuaq in 1910, has been maintained by the Danish and Greenlandic authorities since then. This assessment then allows a greater reflection on the economic and cultural instabilities the Inughuit continue to face. Indeed, this thesis demonstrates that these adversities are inextricably linked to the authorities’ assumption that the Inughuit are ‘primitive’ - later ‘underdeveloped’ - Kalaallit and to the subsequent dispossession of the Inughuit from their political agency. In light of this analysis, this study concludes that colonisation has continuing effects in Avanersuaq today, which should be comprehensively addressed by the competent authorities to ensure the livelihood of the Inughuit as a distinct community.